National development program for Finnish hospital facilities - Reijula, Kari; Hellgren, Ulla-Maija; Holopainen, Riikka; Korhonen, Pirjo; Lappalainen, Sanna; Palomäki, Eero; Palonen, Jari; Autio, Antti; Kjisik, Hennu; Koski, Hannu; Virtanen, Kimmo; Kaleva, Hanna; et al. (SJWEH Supplements, 2008)
To better understand the needs of future hospitals, a nationwide renovation program concerning hospital buildings was recently launched in Finland. Its aims are to develop tools for performing regional long-term plans (including space requirement estimation), to produce criteria for estimating the usability, operability, technical systems, and the basis for physical condition surveys and renovation design, to develop renovation processes for hospital facilities, to develop new tools for property management, to carry out pilot studies with the tools, and to find alternative solutions to owning, financing and managing hospital properties. All these starting points together define the basis for the future spatial needs and operational planning of such premises. The property management and technology of a hospital must be optimized to meet certain requirements, and the planning of renovations must be based on feasibility studies. In addition, increasing attention must be paid to the overall economy and efficiency of owning and managing health care property.
Keywords: development program; Finland; hospital; hospital facility; hospital premise; long-term planning; national development program; property management; renovation; space requirement